The Role of Leadership in Forming Organizational Culture in Islamic Education Institutions - Suwandi Suwandi; Khoirul Umam (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
Organizational culture has a very important role in improving the quality of the organization. If the role of culture can function properly, it can be expected that organizational performance will increase. The purpose of this research article was to understand and describe the role of the principal in the process of forming organizational culture in Madrasah Aliyah Negeri 3 Malang. This research uses a qualitative approach through a case study design using a phenomenological approach. Data collection techniques were carried out by: in-depth interviews, participant observation, and documentation studies. The informant's sampling technique used purposive sampling. Data analysis was carried out by means of: data reduction, data presentation, and drawing conclusions. Meanwhile, checking the validity of the data is carried out using the following criteria: credibility, dependability, and confirmability. The results showed that: First, the leader factor has an important role in the process of forming organizational culture. Second, the process of forming organizational culture occurs through several stages, namely: the adaptation stage, the pattern search stage, the system building stage, and the stage for forming organizational culture as self-identity. The results of this study are expected to be useful for the development of organizational culture theory and also the development of Islamic educational institutions, especially in the development of organizational culture.